THE ROLE OF RELATIONSHIP MARKETING AND SHARIAH COMPLIANCE ON CUSTOMERS’ LOYALTY IN ISLAMIC MICROFINANCE - Anita Rahmawaty (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The purpose of this research is to examine and analize the effect of relationshipmarketing and shariah compliance on customers’ satisfaction and loyalty. This research is a survey research which used a quantitative approach. The data were obtained from 185 respondents by using convenience sampling technique. The research model testing technique used the path analysis approach. The results showed that relationship marketing positively and significantly had effects on customers’ satisfaction and loyalty. In this research, it is found also that shariah compliance is not related to customers’ satisfaction. Nevertheless, it is found that shariah compliance is indirectly able to influence the loyalty through customers’ satisfaction. Thus, the research findings suggest that relationship marketing becomes the important variable that affects the customers’ satisfaction and loyalty.